Effect of propolis on pyruvate kinase and superoxide dismutase activities in doxorubicin-induced tissue damage: Molecular docking analysis - Yilmaz, Seval; Kaya, Emre; Yonar, Harun; Uslu, Harun (Univ Zulia, Facultad Ciencias Veterinarias, 2024)
This study aimed to investigate the effect of propolis on pyruvate kinase (PK) which is a key enzyme in glycolysis and superoxide dismutase (SOD), an antioxidant enzyme on toxicity induced by DOX in different tissues. Using molecular docking, It was looked into how propolis affected the enzymes responsible for glycolysis and the antioxidant system. There was no application in the first group (control). The second group received 100 mgkg -1 day of propolis by gavage needle for 7 days, a single dose of 20 mgkg -1 intraperitoneal DOX to the third group, and propolis+DOX to the fourth group. Two days prior to DOX administration, propolis application began, and it lasted for seven days. PK and SOD activities were determined in liver, heart, kidney, and testis tissues, and molecular docking was applied to ratify the activity of some propolis components (caffeic acid phenethyl ester (CAPE) and Quercetin) on PK and SOD enzymes. When the DOX group was compared with the control group, a decrease in PK and SOD activities were found, and significant difference was found in PK and SOD activities. Administration of DOX decreased PK and SOD activities of liver, heart, kidney, and testis tissues. In conclusion, our study reveals that DOX disrupts glycolysis in rat tissues. CAPE and Quercetin compounds were shown to interact similarly with the cocrystal ligands of PK and SOD. In addition, when the interaction types of these compounds especially on PK and the docking scores obtained were examined, it can be said that they show higher affinity than DOX.
Efecto del propóleo sobre la actividad de la piruvato quinasa y la superóxido dismutase en el daño tisular inducido por doxorrubicina: análisis de acoplamiento molecular
Keywords: Doxorubicin; toxicity; pyruvate kinase; superoxide; dismutase; molecular docking